The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s12105-014-0522-z
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma Cuniculatum of the Esophagus and Tongue: Report of Two Cases, Including TP53 Mutational Analysis

Abstract: Carcinoma cuniculatum (CC) is a rare variant of extremely well differentiated squamous cell carcinoma. We present the clinicopathological features of two cases of CC; one lingual and one esophageal case with a molecular genetic study regarding the TP53 gene mutational status. Case 1 was a 62 year old male with enlarging chronic ulcer in the tongue. Case 2 was a 77 year old male with progressive dysphagia and odynophagia. Both patients were treated surgically. Both tumors showed deeply invaginating, keratin-fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
35
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 17 publications
6
35
0
2
Order By: Relevance
“…The crypts are filled with keratin and contain neutrophil microabscesses. The network of crypts infiltrates adjacent tissues, but often maintains a clear tumorstroma interface [7,22]. These crypts were characteristically found in the present pathology (Fig.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The crypts are filled with keratin and contain neutrophil microabscesses. The network of crypts infiltrates adjacent tissues, but often maintains a clear tumorstroma interface [7,22]. These crypts were characteristically found in the present pathology (Fig.…”
Section: Discussionsupporting
confidence: 66%
“…However, studies examining p53 protein expression in carcinoma cuniculatum have largely been inconclusive. Thavaraj et al found over-expression of p53 in greater than 90% of suprabasal and basal cells in a case of tongue carcinoma cuniculatum [19], while a recent study from Goh et al found minimal p53 expression on immunohistochemistry and no mutations of TP53 on sequence analysis in the case of esophageal carcinoma cuniculatum [22]. This discrepancy is likely attributed to both methodological variation between studies and differing extents of cytologic atypia between tumor samples [23].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, an increasing number of reports describe CC involving head and neck sites, predominantly the oral cavity [2,4,[9][10][11][13][14][15][16][17][18][19][20][21][22]. Table 1 summarizes all reports of CC occurring in the head and neck which could be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Carcinoma cuniculatum of the esophagus is a very rare and extremely well differentiated variant of squamous cell carcinoma, first described in 2005 [1]. Since then, it has been reported in less than 15 cases [2,3]. The etiology is unknown but there have been reported associations with chronic esophageal irritation, achalasia, diverticulum, and prior caustic injury [1,4].…”
mentioning
confidence: 99%